Proposal of computer aided process planning of parts machining using workholding devices - Wataru KOMATSU; Yuki INOUE; Keiichi NAKAMOTO (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2020)
High efficiency machining achieved by shortening preparation time has attracted attention for its many advantages in the field of machining. In order to reduce preparation time, computer-aided process planning (CAPP) is expected to automatically determine machining process parameters such as machining sequence, cutting tools, and cutting conditions. In the author’s previous study, novel machining features are proposed to derive machining process parameters from specific geometric shape patterns of removal volume during a parts machining operation. It is also confirmed that the machining features are recognized by deciding the machining sequence for each machining primitive that is first obtained from the removal volume. However, workholding devices have not been considered to determine the machining sequence or to recognize the machining features in parts machining operation. Workholding devices are generally indispensable for parts machining and are practically important to determine machining sequences. Therefore, this study aims to develop a CAPP system for parts machining considering the use of workholding devices. Two general workholding devices, a machine vise and strap clamps, are assumed for various parts machining operations. Under the limitations of workholding devices, workpiece fixing positions are calculated before the machining features are recognized through allocating the machining sequence. Moreover, the number of fixing changes and the machining time are estimated according to both the workholding device being used and the workpiece fixing positions. Case studies are conducted to confirm the usefulness of the developed CAPP system considering the use of workholding devices. The results reveal that fixing positions are obtained properly for various combinations of workpieces and workholding devices. Furthermore, it is confirmed that the CAPP system has the potential to be effective for automatically determining the machining process parameters of parts machining.